Electrospun composite nanofibers for intermediate-temperature solid oxide fuel cell electrodes. Issue 5 (1st April 2020) - Ahn, Minwoo; Han, Seungwoo; Lee, Jongseo; Lee, Wonyoung
Abstract: Considering the dominant loss associated with surface oxygen exchange reactions among other complex electrochemical processes, the design of an electrode structure for the reasonable operation of solid oxide fuel cells is challenging. The surface oxygen exchange reaction can be considerably facilitated using composite nanofibers containing the electrode, electrolyte, and catalyst. The composite nanofiber electrodes containing Pd show the smallest polarization resistance of 0.031 Ωcm 2 and the maximum power density of 0.7 W/cm 2 at 650 °C, which are 39.2% and 12.5% improved values compare to the catalyst-free composite nanofiber electrodes, respectively. These results provide an facile fabrication strategy for developing high-performance electrodes for use in solid oxide fuel cells.